The occurrence of delirium diagnosis among youth hospitalizations in the United States: A Kids' Inpatient Database analysis. (15th July 2022) - Luccarelli, James; Kalluri, Aditya S.; Thom, Robyn P.; Hazen, Eric P.; Pinsky, Elizabeth; McCoy, Thomas H.
Abstract: Objectives: Delirium is an acute neuropsychiatric condition associated with increased morbidity and mortality. There is increasing recognition of delirium as a substantial health burden in younger patients, although few studies have characterized its occurrence. This study analyzes the occurrence of delirium diagnosis, its comorbidities, and cost among youth hospitalized in the United States. Methods: The Kids' Inpatient Database, a national all‐payers sample of pediatric hospitalizations in general hospitals, was examined for the year 2019. Hospitalizations with a discharge diagnosis of delirium among patients aged 1–20 years were included in the analysis. Results: Delirium was diagnosed in 43, 138 hospitalizations (95% CI: 41, 170–45, 106), or 2.3% of studied hospitalizations. Delirium was diagnosed in a broad range of illnesses, with suicide and self‐inflicted injury as the most common primary discharge diagnosis among patients with delirium. In‐hospital mortality was seven times greater in hospitalizations caring a delirium diagnosis. The diagnosis of delirium was associated with an adjusted increased hospital cost of 8648 per hospitalization, or 373 million in aggregate cost. Conclusions: Based on a large national claims database, delirium was diagnosed in youth at a lower rate than expected based on prospective studies. The relative absence of delirium diagnosis in claims data may reflect underdiagnosis, a failure to code, and/or a lower rate of delirium in general hospitals compared with other settings. Further research is needed to better characterize the incidence and prevalence of delirium in young people in the hospital setting.